Immunoinformatic Analysis of SARS-CoV-2 Nucleocapsid Protein and Identification of COVID-19 Vaccine Targets - Oliveira, Sergio C.; de Magalhães, Mariana T. Q.; Homan, E. Jane (Frontiers in Immunology, 2020)
COVID-19 is a worldwide emergency; therefore, there is a critical need for foundational knowledge about B and T cell responses to SARS-CoV-2 essential for vaccine development. However, little information is available about the targets of immune responses to SARS-CoV-2 other than the spike glycoprotein. In this study, we focus on the SARS-CoV-2 nucleocapsid protein as a suitable candidate target for both vaccine formulations and diagnostic assays. Major B and T cell epitopes of the SARS-CoV-2 N protein are predicted and resulting sequences compared with the homologue immunological domains of other coronaviruses that infect human beings. The most dominant of B cell epitope is located between 176-206 amino acids in the SRGGSQASSRSSSRSRNSSRNSTPGSSRGTS sequence. Further, we identify sequences which are predicted to bind multiple common MHC I and MHC II alleles. Most notably there is a region of potential T cell cross reactivity within the SARS-CoV-2 N protein position 102-110 amino acids that traverses multiple human alpha and betacoronaviruses. Vaccination strategies designed to target the immune response toward these conserved epitope regions could generate immune responses that are cross-reactive across human coronaviruses, with potential to protect or modulate disease. Finally, these predictions can facilitate effective vaccine design against this high priority virus.